INTRODUCTION OF INNOVATION TECHNIQUES IN THE HIGH SCHOOL - O.M. Boichenko; Yu.V. Sidash (Ukrainian Medical Stomatological Academy, 2018)
At present, one of the main features of modern society is its development on the basis of innovations, therefore the purpose of this publication is an attempt to characterize the means, forms and various methods of innovative students' teaching in higher medical institutions of Ukraine, to reveal the specifics of their use in an interactive environment. Modern methods of teaching profiled disciplines among graduates of higher educational institutions are a constant source of observation of foreign and Ukrainian scholars, as many students from near and far abroad are currently receiving education in Ukraine. To ensure the fulfillment of this task there are such documents as a State National Program "Education (Ukraine XXI Century)", the National Doctrine of Education Development (2002), the Law of Ukraine "On Higher Education" adopted in 2014, and the draft Concept for the Development of Education Ukraine for the period 2015-2025 and the draft Strategy for the reform of higher education in Ukraine until 2020 [1]. These documents provide a significant reform of the educational process in order to form a creative professional with a deep knowledge of teaching discipline, strong skills and abilities through the "training of applicants for higher education with modern scientific knowledge using the latest educational and information technologies." Thus, the introduction of modern innovative technologies into the educational process of universities is necessary, first of all, this is connected with the necessity of improving the teaching process, the degradation of the existing traditional educational process, and radical transformations and complex modifications. In time, pedagogy applies a large number of different innovative teaching methods that direct students to the qualitative learning of knowledge, and the development of their intellectual activities, the formation of skills and critical thinking skills, the ability to independently process information, acquire qualities that will be useful in future professional life.